2022
DOI: 10.2147/ijnrd.s389238
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Chronic Kidney Diseases Associated with Proton-Pump Inhibitors Using a Retrospective Hospital-Based Cohort in Thailand

Abstract: Purpose Potential adverse outcomes of Proton pump inhibitors (PPIs) have increasingly been reported. The potential risks to PPIs include hypomagnesemia and chronic kidney disease (CKD). Unlike a real-world electronic medical record (RW-EMR) with active-comparator design, claim databases and special population cohort with non-user design, using in previous studies, resulted in a wide range of strength of association with indication bias. This study aimed to measure the total effect of association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“… 107 , 108 Importantly, studies have also shown that compared with H2RAs, PPI use was significantly associated with an increased risk of developing AKI, CKD, and ESRD. 85 , 91 , 97 , 100 , 104 , 105 , 109 …”
Section: Ast- Associated S Ide ...mentioning
confidence: 99%
“… 107 , 108 Importantly, studies have also shown that compared with H2RAs, PPI use was significantly associated with an increased risk of developing AKI, CKD, and ESRD. 85 , 91 , 97 , 100 , 104 , 105 , 109 …”
Section: Ast- Associated S Ide ...mentioning
confidence: 99%